Neonatal onset propionic acidemia without acidosis: a case report - (:unkn) unknown (TURKISH J PEDIATRICS, 2002)
Propionic acidemia is an inherited disorder of organic acid metabolism characterized by a spectrum of clinical and biochemical findings. The usual presentation is life-threatening ketoacidosis and hyperammonernia. In this report we present a neonate with propionic acidemia presenting with prominent neurologic problems without ketoacidosis. The patient had a serum ammonia level of 3,500 mug/dl which was effectively lowered to normal values in 48 hours by peritoneal dialysis, with remarkable improvement, in neurologic status. However, she developed Candida albicans peritonitis, and sepsis and died of cardiorespiratory failure. Infants who have an early onset propionic acidemia have a high mortality and morbidity rate. In conclusion, propionic acidemia should be in the differential diagnosis of patients with neurologic symptoms and hyperammonemia with or without Acidosis.
Keywords: propionic academia; neonate; peritoneal dialysis